Combining Nanoconfinement in Ag Core/Porous Cu Shell Nanoparticles with Gas Diffusion Electrodes for Improved Electrocatalytic Carbon Dioxide Reduction. Issue 24 (23rd December 2021) - Junqueira, João R. C.; O'Mara, Peter B.; Wilde, Patrick; Dieckhöfer, Stefan; Benedetti, Tania M.; Andronescu, Corina; Tilley, Richard D.; Gooding, J. Justin; Schuhmann, Wolfgang
Abstract: Bimetallic silver‐copper electrocatalysts are promising materials for electrochemical CO2 reduction reaction (CO2 RR) to fuels and multi‐carbon molecules. Here, we combine Ag core/porous Cu shell particles, which entrap reaction intermediates and thus facilitate the formation of C2+ products at low overpotentials, with gas diffusion electrodes (GDE). Mass transport plays a crucial role in the product selectivity in CO2 RR. Conventional H‐cell configurations suffer from limited CO2 diffusion to the reaction zone, thus decreasing the rate of the CO2 RR. In contrast, in the case of GDE‐based cells, the CO2 RR takes place under enhanced mass transport conditions. Hence, investigation of the Ag core/porous Cu shell particles at the same potentials under different mass transport regimes reveals: (i) a variation of product distribution including C3 products, and (ii) a significant change in the local OH ‐ activity under operation. Abstract : Direct comparison of the impact of the CO2 mass transport on the performance of Ag core/porous Cu shell nanoparticles for CO2 reduction between a conventional H‐cell and a gas‐diffusion electrode cell provides the basis for a decrease of the competing hydrogen evolution and boosting the formation of C2 and C3 products.